Seeking legitimation from stakeholders in the implementation of e-procurement- the case of the government of Mauritius - Mohungoo, Idah (Department of Information Systems, 2025)
Legitimation of organizational activities by stakeholders is necessary for an organization's survival. If stakeholders consider organizational activities and the ensuing changes as desirable, appropriate, and acceptable, they will endorse their support and acceptance accordingly, and hence grant their legitimation. The implementation of information systems is among the key organizational activities that stakeholders are likely to support and approve if they hold the belief that the proposed systems and the resulting changes will be beneficial for them. Legitimation of large-scale public sector information systems is becoming increasingly important as information systems (IS) failure in the public sector is still rampant, wasting significant amounts of taxpayer money. There is scarce research on such an important issue in the information system domain. This research investigates the legitimation-seeking process in the implementation of an inter-organizational system, public e-procurement. It identifies the legitimation strategies associated with the activities carried out by the project team to gain the support of the stakeholders including end-users from public sector organizations and suppliers of goods, consultancy, and services from the private sector. The study was conducted in the Republic of Mauritius. The Government of Mauritius entrusted the responsibility of driving the e-procurement project to the Procurement Policy Office which constituted a project team for undertaking the implementation of the inter-organizational information system. The research sets out to understand the experience of both the project team and the end-users who were involved in the implementation of e-procurement in the Government of Mauritius. The research sought to obtain in-depth insight into the meanings and perspectives underlying the legitimation activities of the project team and the perceptions of the stakeholders as the implementation process unfolded. An interpretive research paradigm, along with an abductive research approach were followed and a single case study method was employed. Data was collected through semi-structured interviews, documentary evidence, and observations. The findings of the case study reveal successful legitimation of e-procurement in only a few public sector organizations while legitimation failure was noted in several public bodies. Success was characterized by routinization of e-procurement and consistent use of the online bidding module. The project team undertook several legitimation activities as part of their implementation efforts to obtain stakeholders' legitimation. Successful attempts to gain stakeholders' legitimation contributed to the success of e-procurement implementation. A failure to gain stakeholder legitimation led either to a fallback to former methods of procurement or part-usage of e-procurement. The end users of those public sector organizations that experienced only a part-usage outcome did not routinize e-procurement. Instead, they developed a ‘comply and complain' scenario and depended heavily on the e-procurement implementation team for assistance for doing online bidding. The study presents a set of legitimation strategies which were employed by the project team. The findings also demonstrate the key importance of championship within each public sector organization for seeking and gaining legitimation for inter-organizational information systems. This research has shown that obtaining legitimation is essential in implementing a governance-driven information system that will be accepted by stakeholders. As a contribution to practice, this study emphasizes the importance of leaders building their image and reputation before engaging in the process of acquiring stakeholders' legitimation. The research concludes with the development of a modified legitimation activity model outlining practical suggestions for carrying out legitimation activities in inter-organizational information systems projects.